FICTION WRITING IN WATTPAD AS A LEARNING MEDIA FOR IMPROVING THE STUDENTS’ WRITING SKILL IN ENGLISH LANGUAGE TEACHING DEPARTMENT UNU PURWOKERTO - Dinar Faiza; Meilina Haris Mayekti (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
The research contains the analysis of the use of Wattpad  for  practicing  a fiction writing  as an alternative learning media and method to improve the students’ writing skills, It was conducted  in English Language Teaching Department, UNU Purwokert by taking 37 students as research object. This study used mix method approach by using qualitative and quantitative. Data collection was carried out  by purposive sampling where researchers collected data through pre-test and post-test, questionnaires and interview to 37 students. It aimed to perceive the improvement of students’ writing skill, the students’ perception about Wattpad in building writing habit, interest, motivation and confidence in writing. The result of study showed there are improvements in writing skill after treatment mainly in idea/imagination development, organization such as building plot, characterizations and conflict. For grammar wise, it showed the improvement in vocabulary, part of speech and tenses, The activity also stimulates students' motivation and confidence to learn English, especially in terms of writing. It affects to the classroom atmosphere between lecturers and students because the class becomes more lively and interactive.